Aplicación del diseño biofílico en el modelo arquitectónico deportivo, recreativo y cultural. (2022)
The biophilic design applied to the public competition for the design of a sports, recreational and cultural center in the Fontanar River Park - Bogotá, arises as a consequence of the excessive growth of urban spaces disconnected from natural environments. The work of degree seeks to establish the importance of interior design from biophilic design, understood as a need for connection and innate attraction of the human being with nature.As a result of conceptualizing biophilia, and determining its most appropriate patterns for the application proposal, the application is made from different scales and factors (scale, climate, proportion, demography). As a result, different biophilic patterns were applied, related to the vegetation of the local context in an architectural proposal designed inside and outside, achieving functional and holistic spaces.